Anxiety : meditations on the anxious mind - School of Life (Business enterprise) (London : The School of Life Press, 2020)
Far more than we tend to realise, we're all - in private - deeply anxious. This is a guide to our anxious minds, offering a route to calm, self-compassion and mental well-being.
Formerly CIP.
Keywords: Anxiety